2015
DOI: 10.1039/c5sm00602c
|View full text |Cite
|
Sign up to set email alerts
|

Complementary light scattering and synchrotron small-angle X-ray scattering studies of the micelle-to-unimer transition of polysulfobetaines

Abstract: AB and ABA di- and triblock copolymers where A is the hydrophilic poly(oligoethylene glycol methacrylate) (POEGMA) block and B is a thermo-responsive sulfobetaine block [2-(methacryloyloxy) ethyl] dimethyl-(3-sulfopropyl) ammonium hydroxide (PDMAPS) were synthesised by aqueous RAFT polymerisation with narrow dispersity (ĐM ≤ 1.22), as judged by aqueous SEC analysis. The di- and triblock copolymers self-assembled in salt-free water to form micelles with a PDMAPS core and the self-assembly of these polymers was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 55 publications
1
24
0
Order By: Relevance
“…Calibration was achieved with filtered toluene and the background was measured with filtered solvent (NaCl 0.1 M). The hydrodynamic radius, R h , and aggregation number, N agg of the self‐assemblies were calculated using the algorithm method as previously reported . TEM samples were prepared on graphene oxide (GO)‐coated carbon grids, which allows high contrast TEM images to be acquired without staining.…”
Section: Methodsmentioning
confidence: 99%
“…Calibration was achieved with filtered toluene and the background was measured with filtered solvent (NaCl 0.1 M). The hydrodynamic radius, R h , and aggregation number, N agg of the self‐assemblies were calculated using the algorithm method as previously reported . TEM samples were prepared on graphene oxide (GO)‐coated carbon grids, which allows high contrast TEM images to be acquired without staining.…”
Section: Methodsmentioning
confidence: 99%
“…141143 In two recent studies N agg data obtained via SLS has been compared to that calculated from SAXS analyses, with good agreement providing greater confidence in the model used for the latter technique. 142,143 …”
Section: Characterization Techniquesmentioning
confidence: 99%
“…Polymeric nanoparticles comprising block copolymers with cationic, 28,34,[36][37][38] anionic 25,39,40 and zwitterionic 41,42 character have been synthesised via PISA. In both dispersion and emulsion-based PISA systems, it has been shown that the morphology is influenced by the charge density of the solvophilic block -if the charge density is too high, only spheres can form due to the strong repulsive forces between the chains on decreasing the curvature of the interface between the core and the continuous phase.…”
Section: Introductionmentioning
confidence: 99%